2017
DOI: 10.1038/bjc.2017.117
|View full text |Cite
|
Sign up to set email alerts
|

Text-message Reminders in Colorectal Cancer Screening (TRICCS): a randomised controlled trial

Abstract: Background:We investigated the effectiveness of a text-message reminder to improve uptake of the English Bowel Cancer Screening programme in London.Methods:We performed a randomised controlled trial across 141 general practices in London. Eight thousand two hundred sixty-nine screening-eligible adults (aged 60–74 years) were randomised in a 1 : 1 ratio to receive either a text-message reminder (n=4134) or no text-message reminder (n=4135) if they had not returned their faecal occult blood test kit within 8 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 28 publications
(37 reference statements)
0
69
1
Order By: Relevance
“…Regional differences in uptake, in particular the persistent and strong social gradient in London, are very striking considering the vast majority of initiatives and interventions taken place there; for example, a text message trial [12] , many community engagement initiatives with different ethnic groups [18] and national ASCEND trials [7] . Further research using spatial classification based on population density and location characteristics (urban vs. rural) may provide further insights into the better understanding of inequalities in London which are not usually a target of epidemiological research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regional differences in uptake, in particular the persistent and strong social gradient in London, are very striking considering the vast majority of initiatives and interventions taken place there; for example, a text message trial [12] , many community engagement initiatives with different ethnic groups [18] and national ASCEND trials [7] . Further research using spatial classification based on population density and location characteristics (urban vs. rural) may provide further insights into the better understanding of inequalities in London which are not usually a target of epidemiological research.…”
Section: Discussionmentioning
confidence: 99%
“…Uptake of the first-time invitations has emerged as a critical performance factor in light of evidence that people who completed their test kit at least once continued to do so in subsequent screening rounds [10] . Indeed, many recent interventions to promote uptake were only seen to be effective among this ‘first-time’ group as opposed to those receiving repeat invitations [11] , [12] .…”
Section: Introductionmentioning
confidence: 99%
“… 28 A recent trial of text message reminders found no significant main effect but a significant 5% increase in uptake among first-time invitees. 29 …”
Section: Uptakementioning
confidence: 99%
“…Text message reminders have been shown to improve cancer screening uptake. 16 , 23 Also, there is encouraging evidence that text messages can be used in primary care to monitor acute and chronic conditions, and that this reduces the cost of care, improves patient adherence, and promotes continuity of care. 15 Primary care physicians in a survey study in Switzerland reported that the use of text messages improved patient follow-up.…”
Section: Discussionmentioning
confidence: 99%